2020
DOI: 10.22146/ijcpa.507
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Temulawak (Curcuma xanthorrhiza Roxb.) and its Classification with Chemometrics

Abstract: Temulawak (Curcuma xanthorrhiza Roxb.) or Javanese turmeric is one of the medicine plants from Indonesia, which contains curcuminoid and xanthorrhizol. These compounds have large biological activity, such as antioxidant capacity. The location of this plant grows, affects the variance of the active compound which causes the changes in its activity. This study aims to evaluate antioxidant capacity, total phenolic, and total flavonoid content (TPC and TFC) of the sample collected from different markets, and to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 16 publications
0
9
0
8
Order By: Relevance
“…The study revealed that the tested extract of C. xanthorrhiza has a relatively active antioxidant activity with an IC 50 value of 87.01 ppm. Meanwhile, Widyastuti et al [ 75 ] examined the antioxidant properties of C. xanthorrhiza harvested from different locations. The methanol extract of C. xanthorrhiza from various places has been assessed for its antioxidant properties along with total phenolic and total flavonoid composition.…”
Section: Pharmacological Activities Of C Xanthorrhizamentioning
confidence: 99%
See 2 more Smart Citations
“…The study revealed that the tested extract of C. xanthorrhiza has a relatively active antioxidant activity with an IC 50 value of 87.01 ppm. Meanwhile, Widyastuti et al [ 75 ] examined the antioxidant properties of C. xanthorrhiza harvested from different locations. The methanol extract of C. xanthorrhiza from various places has been assessed for its antioxidant properties along with total phenolic and total flavonoid composition.…”
Section: Pharmacological Activities Of C Xanthorrhizamentioning
confidence: 99%
“…The methanol extract of C. xanthorrhiza from various places has been assessed for its antioxidant properties along with total phenolic and total flavonoid composition. The result showed that C. xanthorrhiza has potent antioxidant activity and its level is apparently affected by different harvesting areas [ 75 ]. The discovery validates the diverse uses and effectiveness of this herb over various traditional areas and populations ( Table 1 ) and gives possible suggestions on the levels of active molecules depending on the location of cultivation.…”
Section: Pharmacological Activities Of C Xanthorrhizamentioning
confidence: 99%
See 1 more Smart Citation
“…Curcuma xanthorrhiza Roxb atau temulawak adalah Tanaman yang telah banyak dimanfaatkan sebagai jamu tradisional (Widyastuti et al, 2020). Pada tabel 1 diketahui bahwa temulawak mengandung kurkumin, hal ini sesuai dengan penelitian yang menyatakan bahwa temulawak merupakan tanaman obat dari Indonesia yang mengandung senyawa kurkumin dan xanthorrhizol yang memiliki khasiat di bidang kesehatan (Widyastuti et al, 2020).Uji antioksidan dalam artikel menggunakan metode DPPH radikal bebas untuk mendapatkan nilai IC 50 dengan menggunakan spektrofotometer UV-VIS dengan range panjang gelombang tertentu.…”
Section: Hasil Dan Pembahasanunclassified
“…Seperti yang dilakukan oleh Mariane., (2018) [20] yang menemukan aktivitas antioksidan dalam ekstrak rimpag temu giring (Curcuma heyneana) yakni sebesar 102,15 ppm. Serta penelitian oleh Widyastuti., (2020) [21] yang menemukan aktivitas antioksidan pada rimpang temu lawak (Curcuma xanthorizae) dari berbagai daerah berkisar 32,54 ± 0,92 µg/mL hingga 77,19 ± 0,74 µg/mL. Sedangkan rimpang kunyit (Curcuma longa) memiliki aktivtas antioksidan sebesar 48,33 ppm [22] (septiana 2015).…”
Section: Gambar 3 Reaksi Dpph Dengan Antioksidanunclassified